The System Development of Durian Types Classification Using the Color Intensity Technique - Witthaya Boonsuk (Mathematical Statistician and Engineering Applications, 2023)
The purpose of this study was to develop software to categorize Durian types applying color categorization. The principle of the software was to analyze the mean of color intensity which focused on the green and blue color groups. The results of efficiency assessment were gathered from the developed Algorithm.There were 9 groups of the sample images which each group contained 5 images, 45 images in total. The precision of Group 1: Mon Thong was 80%, Group 2: Kan Yao was 80%, Group 4: Long Lab Lae was 80%, 5: Nok Yip was 80%, 6: Kradum Thong was 80%, Group7: Kop Chainam was 80%, Group 8: Thong Yoi Chat was 80% and Group 9: Phuang Mani was 80%, the average mean was 80%. The overview of the developed software was considered at a good level which confirmed that the color comparison was rather precise. In addition, it would be suitable to be applied in the analysis of the image color intensity.